Smart Universities Concepts, Systems, and Technologies (Smart Innovation, Systems and Technologies,, 2018)
This book presents peer-reviewed contributions on smart universities by various international research, design and development teams. Smart university is an emerging and rapidly evolving area that creatively integrates innovative concepts; smart software and hardware systems; smart classrooms with state-of-the-art technologies and technical platforms; smart pedagogy based on modern teaching and learning strategies; smart learning and academic analytics; as well as various branches of computer science and computer engineering. The contributions are grouped into several parts: Part 1-Smart Universities: Literature Review and Creative Analysis, Part 2-Smart Universities: Concepts, Systems and Technologies, Part 3-Smart Education: Approaches and Best Practices, and Part 4-Smart Universities: Smart Long Life Learning. The book is a valuable source of research data and findings, design and development outcomes, and best practices for faculty, scholars, Ph.D students, administrators, practitioners and anyone interested in the rapidly growing areas of smart university and smart education.